PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA BRAND MAKANAN CEPAT SAJI ( studi kasus di KFC di Surabaya ) - Andriani, Andriani; Achmad Daengs GS; Retno Susanti (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The purpose of this study was to determine the effect of KFC's brand image and product quality on purchasing decisions in Surabaya. Samples were taken as many as 150 respondents from KFC consumers who had consumed KFC at least 2 times in their lives in Surabaya. The author hopes that this research will be useful for the future of the company and become a science for Indonesian education. In connection with this research, the authors apply quantitative research methods to examine the population or sample. Then the data generated from quantitative research is analyzed so as to produce data that can be used for the advancement of the company and become a knowledge archive for the community. The results of this study indicate that brand image has a significant positive effect on purchasing decisions and product quality also has a significant positive effect on purchasing decisions for KFC in Surabaya.